Facile synthesis of alfa-nickel hydroxide by an ultrasound-assisted method and its application in energy storage devices - Abbas, Syed Asad; Iqbal, Muhammad Ibrahim; Kim, Seong-Hoon; Khan, Hassnain Abbas; Jung, Kwang-Deog (ELSEVIER SCIENCE BV, 2019)
Alfa-nickel hydroxide is prepared by a high-energy ultrasound (sonochemical) method that enables precise control over the reaction process. The prepared alfa-nickel hydroxide can be easily transformed into the beta phase of nickel hydroxide by adjusting the reaction time. BET analysis of the alfa-nickel hydroxide prepared in this method reveals a very high specific surface area (384 m(2) g(-1)), extraordinarily high pore volume (0.77 cm(3) g(-1)) and mesoporous structure. Scanning electron microscopy images show that the alfa-nickel hydroxide has a worm-like morphology, whereas the beta phase exhibits a petal-like morphology. To investigate the electrochemical properties of the nickel hydroxide, it is first calcined to nickel oxide at 250 degrees C, and then the capacitance of the resulting NiO sample is measured by cyclic voltammetry, galvanostatic charge-discharge measurements and electrochemical impedance spectroscopy. When alfanickel hydroxide is converted to NiO, the BET surface area increases slightly, due to dehydroxylation and calcination at a relatively low temperature. However, the pore volume remains nearly constant. The high specific capacitance of 955 F g(-1) at the scan rate of 10 Ag-1 is obtained for the NiO sample. The presence of mesopores and the high specific surface area enhance ion transport during the charge and discharge processes to enable high energy storage. (C) 2018 Elsevier B. V. All rights reserved.
Keywords: SURFACE-AREA; NIO; SUPERCAPACITOR; PERFORMANCE; NANOSHEETS; WATER; NANOSTRUCTURES; BETA-NI(OH)(2); MICROSPHERES